Exploration of GGTase-I substrate requirements. Part 2: Synthesis and biochemical analysis of novel saturated geranylgeranyl diphosphate analogs. Issue 15 (1st August 2016) - Temple, Kayla J.; Wright, Elia N.; Fierke, Carol A.; Gibbs, Richard A.
Graphical abstract: Abstract: Protein prenylation is a type of post-translational modification that aids certain proteins in localizing to the plasma member where they activate cell signaling. To better understand the isoprenoid requirements and differences of FTase and GGTase-I, a series of saturated geranylgeranyl diphosphate analogs were synthesized and screened against both mammalian FTase and GGTase-I. Of our library of compounds, several analogs proved to be substrates of GGTase-I, with11d having a k rel  = 0.95 when compared to GGPP ( k rel  = 1.0).